Self-Expandable Metal Stent in the Management of Malignant Airway Disorders - Bai, Yang; Zhan, Ke; Chi, Jing; Jiang, JinYue; Li, Shuang; Yin, Yuting; Li, Yishi; Guo, Shuliang (Frontiers in Medicine, 2022)
Background: Self-expanding metallic stent (SEMS) is a palliative therapy for patients with malignant central airway obstruction (CAO) or tracheoesophageal fistula (TEF). Despite this, many patients experience death shortly after SEMS placement. Aims: We aimed to investigate the effect of SEMS on the palliative treatment between malignant CAO and malignant TEF patients and investigate the associated prognostic factors of the 3-month survival. Methods: We performed a single-center, retrospective study of malignant CAO or TEF patients receiving SEMS placement. Clinical data were collected using the standardized data abstraction forms. Data were analyzed using SPSS 22.0. A two-sided P-value < 0.05 was statistically significant. Results: 106 malignant patients (82 CAO and 24 TEF) receiving SEMS placement were included. The body mass index (BMI), hemoglobin levels, and albumin levels in the malignant TEF group were lower than in the malignant CAO group (all P < 0.05). The procalcitonin levels, C-reactive protein levels, and the proportion of inflammatory lesions were higher in the malignant TEF group than in the malignant CAO group (all P < 0.05). The proportion of symptomatic improvement after the SEMS placement was 86.8% in the malignant TEF group, whereas 50.0% in the malignant CAO group, with a significant difference (P = 0.000). Three months after SEMS placement, the survival rate at was 67.0%, significantly lower in the malignant TEF group than in the malignant CAO group (45.8% vs. 73.2%, P = 0.013). Multivariate analysis revealed that BMI [odds ratio (OR) = 1.841, 95% certificated interval (CI) (1.155-2.935), P = 0.010] and neutrophil percentage [OR = 0.936, 95% CI (0.883-0.993), P = 0.027] were the independent risk factors for patients who survived three months after SEMS placement. Conclusions: We observed symptom improvement in malignant CAO and TEF patients after SEMS placement. The survival rate in malignant TEF patients after SEMS placement was low, probably due to aspiration pneumonitis and malnutrition. Therefore, we recommend more aggressive treatment modalities in patients with malignant TEF, such as strong antibiotics, nutrition support, and strategic ventilation. More studies are needed to investigate the prognostic factors in patients with malignant airway disorders receiving SEMS placement.